Pedagogia do armário: identidade, pertencimento e apropriação do futebol por torcedores homossexuais - Jose Aelson da Silva Junior (2018)
Gay men participation in soccer assistance, in a scientific aim, represents a historical and cultural contrast which highlights a shift on this sports logic as a space of resistance and conservation of a heteronormative order or, more than that, of a model of an expected and accepted masculinity in the soccer field. The gaps on this subject justifies the relevance in discussing the cheering act and the soccer game, as spheres for leisure practicing, where the domination of a certain masculinity is evidenced and valued. This said, the following issues were entrusted to the goals of this study: (1) how gay spectators fit into this space; and, from the understanding of this scenario, (2) which speeches are made about homosexuality, homophobia and soccer by them. To reach such aim, there has been established a dialogue with male and female authors whose production is included in Cultural Studies, Queer and Feminist, to the theoretical framework composition used for the understanding of the key concepts, as well as works that have constituted "a field of Studies about Soccer in Brazil. This research is qualitative in nature description and data analysis, in which the field of work made use of semi-structured interview. The records of the fifteen subjects interviewed were organized into thematic frames, in order to an understanding of the objectives defined, a priori, in the intersections of the speeches. It can be understood that none of the informants are unrelated to the homophobia in the stadiums and in the experience of cheering, even though some of them do not recognize it in soccer games, by assigning other senses to swearing and behaviors experienced in such places. In general, they appropriate these territories, produce and reproduce heterosexist and homophobic behavior in a similar aspect to other spectators, aligned to a heteronormative logic of the cheering act. It was helpful to metaphorically classify them as mimetic spectators, when reflecting on the experiences that they reported living within soccer and their factionalism. The term "Mimetic" is understood, in this research, as a form of protection and defense in a reception and inclusion procedures among "the equal", sustained by referential of masculinities and manhood typical for the soccer stadiums, where the mimetic spectator resembles the other fans/spectators, driven by different interests linked to the experience of such form of leisure.